Nanostructured Materials based on Noble Metals for Advanced Biological Applications - Venditti, Iole (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue "Nanostructured Materials Based on Noble Metals for Advanced Biological Applications" highlights the recent progress in gold and silver nanomaterials preparation/synthesis as well as their innovative applications in advanced applications, such as in nanomedicine and nanosensors. It is nowadays generally accepted that nanostructured noble metals allow the production of highly competitive materials. In fact, a specific design and rather simple and reliable preparation techniques can be used to obtain optimized material uses and possibilities for their reusability. One expects amazing future developments for these nanotechnologies from research laboratories to key industrial areas. The Guest Editor and the MDPI staff are therefore pleased to offer this Special Issue to interested readers, including researchers, graduate and PhD students as well as postdoctoral researchers, but also to the entire community interested in the wide world of nanomaterials.